2004
DOI: 10.1046/j.1439-0523.2003.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic relationships among Cucumis spp. by SSR and RAPD marker analysis

Abstract: The first successful production of a sterile interspecific hybrid obtained from a cross between Cucumis hystrix Chakr. (2n = 2x = 24) and Cucumis sativus var. sativus L. (2n =2x = 14), and its subsequent fertility restoration through chromosome doubling provide an effective means for investigating genetic relationships among Cucumis spp. In this study, random amplified polymorphic DNA (RAPD) and simple sequence repeat (SSR) markers were used to investigate relationships among C. s. var. sativus L., C. s. var. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…In terms of coefficients of variation (CV) per band, RAPDs exhibited lower CVs than did either isozymes or SSRs in Cucumis with moderate congruence between results generated by each marker class. In contrast, Zhuang et al (2004) reported a high degree of congruence between genetic relationships revealed by RAPDs and SSRs among Cucumis taxa.…”
Section: Germplasm Characterizationmentioning
confidence: 77%
See 1 more Smart Citation
“…In terms of coefficients of variation (CV) per band, RAPDs exhibited lower CVs than did either isozymes or SSRs in Cucumis with moderate congruence between results generated by each marker class. In contrast, Zhuang et al (2004) reported a high degree of congruence between genetic relationships revealed by RAPDs and SSRs among Cucumis taxa.…”
Section: Germplasm Characterizationmentioning
confidence: 77%
“…(2n=2x=24; Chinese origin) (Kirkbride 1993;Chen et al 1997b). Molecular-marker analyses have recently confirmed that these two species form a coherent group in relation to subgenus Melo (Zhuang et al 2004). This is also reflected in the development of a stable amphidiploid hybrid, C. X hytivus Chen & Kirkbride, derived from the artificial hybridization of these two species (Chen and Kirkbride 2000).…”
Section: Cucumismentioning
confidence: 88%
“…The development of genetic markers associated with cucumber has a narrow genetic base Staub et al, [9] which limits development of new cucumber cultivars. To date, the degree of genetic diversity in cucumber has been assessed with a number of DNA markers Zhuang et al, [10] which provide useful information for cucumber cross breeding. Molecular markers such as RAPD and SSRs have been employed for determination of genetic diversity in African cucumber (Cucumis sativus L.) Ahmad Mliki et al, [11].…”
Section: Introductionmentioning
confidence: 99%
“…These markers have been used to assess genetic diversity and relationships among cucumber cultivars, as they are not influenced by environmental conditions. Although some studies made use of one or more DNA markers (Danin-Poleg et al, 2001;Zhuang et al, 2004;Staub et al, 2005;Sikdar et al, 2010), few reports have examined the correlation between genetic diversity and agronomic traits, especially fruit traits.…”
Section: Introductionmentioning
confidence: 99%